2020
DOI: 10.23937/2474-3658/1510143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Burden and Intervention Strategies of TB-HIV Co-Infection in West Africa

Abstract: The co-infection of Tuberculosis with HIV has continually placed an immense burden on public health systems, mostly in Low and Middle Income (LMIC) countries. We present a geographical analysis of current intervention programs and prevalence rates in two West African states (Ghana and Nigeria). In some regions with higher co-infection rates and dense population, interventions were seen to be relatively lower, relative to other less densely populated regions. A hybrid mathematical and agent-based model for dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…HIV infection has emerged as the principal cause of human immunodepression exposing people living with HIV to opportunistic diseases such as Mtb . The geographical overlapping of the two diseases had increased the number of cases of HIV/TB co-infection causing an immense and continuous burden on public health systems, mostly in Low and Middle Income Countries (LMIC) [ 1 ]. In fact, people living with HIV are about 30 times more likely to develop active TB, due to compromised immunity [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…HIV infection has emerged as the principal cause of human immunodepression exposing people living with HIV to opportunistic diseases such as Mtb . The geographical overlapping of the two diseases had increased the number of cases of HIV/TB co-infection causing an immense and continuous burden on public health systems, mostly in Low and Middle Income Countries (LMIC) [ 1 ]. In fact, people living with HIV are about 30 times more likely to develop active TB, due to compromised immunity [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…TB has been described as one of the diseases leading to death, and Nigeria as a nation is among the countries leading in TB and TB/HIV co-infection [2]. It was further shown that 8% of global cases of TB are found in Africa first approximately 2 billion cases.…”
Section: Introductionmentioning
confidence: 99%